The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/s0100-29452014000500032
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização anatômica e citométrica em biribazeiro (Rollinia mucosa [Jacq.])

Abstract: RESUMO -O biribazeiro (Rollinia mucosa [Jacq.]) é uma frutífera nativa da América Central e América do Sul que se destaca das demais espécies do gênero por apresentar frutos grandes e comestíveis. Tendo em vista que pouco se conhece a respeito da anatomia da planta, tipo de reserva da semente, como também sobre o conteúdo de DNA de espécies da família anonáceas, este trabalho teve por objetivos caracterizar histoquimicamente as sementes e anatomicamente as plântulas, e determinar o conteúdo de DNA de biribazei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…This was also observed in seeds of Acrocomia aculeata (Ribeiro et al, 2010). However, no difficulties were found in this study for the analysis of results, although atemoya seeds had predominantly lipid reserves, in the same manner as other species of the family Annonaceae, such as A. muricata (Kimbonguila et al, 2010), A. squamosa (Masruri et al, 2012) and Rollinia mucosa (Soares et al, 2014). Because of factors relative to the standardization of the method, different results are obtained between genera of the same family and even between species of the same genus.…”
Section: Resultsmentioning
confidence: 64%
“…This was also observed in seeds of Acrocomia aculeata (Ribeiro et al, 2010). However, no difficulties were found in this study for the analysis of results, although atemoya seeds had predominantly lipid reserves, in the same manner as other species of the family Annonaceae, such as A. muricata (Kimbonguila et al, 2010), A. squamosa (Masruri et al, 2012) and Rollinia mucosa (Soares et al, 2014). Because of factors relative to the standardization of the method, different results are obtained between genera of the same family and even between species of the same genus.…”
Section: Resultsmentioning
confidence: 64%
“…The genome size reported here is similar to Lorenzoni (2016) : 2C = 5.42 pg (±0.12) with 15 accessions of unknown origin of hexaploid cultivated plants maintained at the Federal University of Espírito Santo (Alegre, ES, Brazil). The other two studies showed divergences in the size of the A. mucosa genome ( Soares et al, 2014 ; Leitch et al, 2019 ), but methods, sample sizes and provenances are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Annona mucosa has two ploidy levels: 2 n = 4x = 28 in a population in Peru ( Maas et al, 1992 ) and 2 n = 6x = 42 in domesticated populations in Brazil ( Morawetz, 1986b ; Lorenzoni, 2016 ). The species also appears to present genome size variation (2C = 4.77, 5.42 and 6.00 pg) ( Soares et al, 2014 ; Lorenzoni, 2016 ; Leitch et al, 2019 ). However, the cytogenetic and genome size studies of A. mucosa have many gaps, such as the absence of exact collection location and the lack of information about the phenotype of the fruits in the published studies.…”
Section: Introductionmentioning
confidence: 99%
“…Annona mucosa has two ploidy levels: 2n = 4x = 28 in probably wild populations in Peru (Maas & al., 1992) and 2n = 6x = 42 in domesticated populations in Brazil (Morawetz, 1986;Lorenzoni, 2016). The species also appears to be variable in genome size (2C = 4.77, 5.42 and 6.00 pg) (Soares & al., 2014;Lorenzoni, 2016;Leitch & al., 2019). Recent studies identified wild populations of A. mucosa in Mexico (Segura & al., 2018;Escobedo-López & al., 2019).…”
Section: Zingiberaceaementioning
confidence: 99%